2000
DOI: 10.1046/j.1365-2567.2000.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E supplementation increases T helper 1 cytokine production in old mice infected with influenza virus

Abstract: SUMMARYCompared with young mice, old mice infected with in¯uenza virus have signi®cantly higher pulmonary viral titres, although these can be reduced signi®cantly with dietary vitamin E supplementation. T helper 1 (Th1) cytokines, especially interferon-c (IFN-c), play an important role in defending against in¯uenza infection. However, there is an age-associated loss of Th1 cytokine production. Prostaglandin E 2 (PGE 2 ) production, which increases with age, can modulate the T helper cell function by suppressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 35 publications
5
110
1
Order By: Relevance
“…Old mice fed 30 ppm of vitamin E had higher viral titres than young mice fed the same way. Influenza lung viral titres were lower in old mice fed 500 ppm vitamin E compared with the age-matched mice fed 30 ppm vitamin E. In a subsequent study, Han et al (126) showed that the preventive effect of vitamin E was not observed following supplementation with other antioxidant compounds such as glutathione, melatonin or strawberry extract. Furthermore, vitamin E prevented the weight loss associated with influenza infection, while other dietary antioxidant treatments had no effect on weight loss.…”
Section: Vitamin Ementioning
confidence: 98%
See 1 more Smart Citation
“…Old mice fed 30 ppm of vitamin E had higher viral titres than young mice fed the same way. Influenza lung viral titres were lower in old mice fed 500 ppm vitamin E compared with the age-matched mice fed 30 ppm vitamin E. In a subsequent study, Han et al (126) showed that the preventive effect of vitamin E was not observed following supplementation with other antioxidant compounds such as glutathione, melatonin or strawberry extract. Furthermore, vitamin E prevented the weight loss associated with influenza infection, while other dietary antioxidant treatments had no effect on weight loss.…”
Section: Vitamin Ementioning
confidence: 98%
“…Vitamin E supplementation (125,126) has also been shown to reduce lung viral titres following influenza infection. The evidence thus far suggests that improved immune response following nutrient intervention might have clinical significance for this age group.…”
Section: Multivitamin/mineral Supplementationmentioning
confidence: 99%
“…For example, faced with a drop in the abundance of a preferred resource, a species might shift to an alternative resource that happens to have a different vitamin E content. Vitamin E has multiple physiological roles, including as an antioxidant and regulator of the immune system [23]. Hypothetically, a shift in vitamin E intake might affect regulation of oxidative balance as well as response to a parasite.…”
mentioning
confidence: 99%
“…No similar study was found to support this observation. It has been suggested that, αTmight reduce inflammatory pain by decreasing plasma NO (Nitric oxide), TNF-α (Tumor necrosis factor -alpha), PGE 2 (Prostaglandin E type 2) [41][42][43][44] . In addition, KT also reduces inflammatory mediators by inhibiting the prostaglandin synthesis by competitively blocking cyclooxygenase (COX) 40,45 .…”
Section: Antinociceptive Effectmentioning
confidence: 99%